Spiritual Criminology: The Case of Jewish Criminology - Ronʾel, Nati (International journal of offender therapy and comparative criminology, 2018)
Throughout the ages and in most cultures, spiritual and religious thinking have dealt extensively with offending (person against person and person against the Divine), the response to offending, and rehabilitation of offenders. Although modern criminology has generally overlooked that body of knowledge and experience, the study of spirituality and its relation to criminology is currently growing. Frequently, though, it is conducted from the secular scientific perspective, thus reducing spiritual knowledge into what is already known. Our aim here is to present a complementary perspective; that is, spiritual criminology that emerges from the spiritual perspective. Following a description of the state-of-the-art in criminological research concerning spirituality and its impact upon individuals, we focus on Jewish criminology as an illustrative case study, and present a spiritual Jewish view on good and evil, including factors that lead to criminality, the issue of free choice, the aim of punishment and societal response, crime desistance, rehabilitation, and prevention. The proposed establishment of spiritual criminology can be further developed by including parallel schools of spirituality, to create an integrated field in criminology.